POTENTIAL APPLICATION OF LIGNITE AS ADSORBENTS IN INDUSTRIAL WASTEWATER TREATMENT: A MINI REVIEW - Galuh Yuliani (Buletin Sumber Daya Geologi, 2015)
Low rank coal (or lignite) is a low grade, wet, low cost and highly abundant coal. The high moisture content of lignite limits its application as high-heating value fuel and also creates barrier for its export as fuel. However, this property should not necessarily hinder its use in the water industry. Similar to activated carbons, lignite has the theoretical ability to treat the wastewater by adsorbing contaminants from aqueous solution. This review paper highlights the potential use of lignite in wastewater treatment industry.